Control of Asthma in Canada: Failure to Achieve Guideline Targets - Kenneth R Chapman; Pierre Ernst; A Grenville; P Dewland; Sabrina Zimmerman (Canadian Respiratory Journal)
OBJECTIVE: To assess the degree of asthma control achieved by patients with asthma in Canada and to describe the impact of poor asthma control.